Energy Preserves Task Scheduling In Heterogeneous Virtual Machine Framework - Deepa, RV; Ramaraj, E (International Journal of Computer Sciences and Engineering, 2018)
-In Virtual machine, Energy conservation is the major problem and it provides benefits such as reducing costs, increased reliability of the system and it also provides protection to the environment. Energy–aware scheduling is used to achieve these benefits. Existing energy-aware scheduling algorithms are not real time task oriented and also it lacks in system schedulability. Vacation queuing model is used for real-time, a periodic, independent task to solve this problem. The system which is proposed here can achieve energy optimization by combining the virtual machine resources with current exploitation. The eminence of hardware and nodes are well-organized with virtual network topologies. Vacation system is implemented with sojourn time to guarantee the schedulability of real-time tasks, efficiently. Simultaneously, energy consumption via dynamic VMs consolidation is concentrated. There are two strategies i.e. scale up and scale down to achieve a suitable trade-off sandwiched between task’s schedulability and energy preservation. Energy conservation is achieved by switching the active host to sleep mode when the system does not perform any action. The task should be completed within the deadline and each user must provide the deadline to avoid rejection. The deadline is analyzed and acknowledgement is provided to the scheduler for each task completion.